Is the equivalence principle doomed forever to Dante's Inferno on account of quantum mechanics? - Accioly, Antonio [UNESP]; Aldrovandi, Ruben [UNESP]; Paszko, Ricardo [UNESP] (World Scientific Publishing, 2006)
It is commonly assumed that the equivalence principle can coexist without conflict with quantum mechanics. We shall argue here that, contrary to popular belief, this principle does not hold in quantum mechanics. We illustrate this point by computing the second-order correction for the scattering of a massive scalar boson by a weak gravitational field, treated as an external field. The resulting cross-section turns out to be mass-dependent. A way out of this dilemma would be, perhaps, to consider gravitation without the equivalence principle. At first sight, this seems to be a too much drastic attitude toward general relativity. Fortunately, the teleparallel version of general relativity - a description of the gravitational interaction by a force similar to the Lorentz force of electromagnetism and that, of course, dispenses with the equivalence principle - is equivalent to general relativity, thus providing a consistent theory for gravitation in the absence of the aforementioned principle. © World Scientific Publishing Company.
Keywords: Equivalence principle; General relativity; Quantum mechanics; Teleparallel gravity